The Semi-automatic Construction of the Polish Cyc Lexicon - Pohl, Aleksander (Investigationes Linguisticae, 2010)
In this paper we discuss the problem of building the Polish lexicon for the Cyc ontology. As the ontology is very large and complex we describe semi-automatic translation of part of it, which might be useful for tasks lying on the border between the fields of Semantic Web and Natural Language Processing. We concentrate on precise identification of lexemes, which is crucial for tasks such as natural language generation in massively inflected languages like Polish, and we also concentrate on multi-word entries, since in Cyc for every 10 concepts, 9 of them is mapped to expressions containing more than one word.